Fenomena Fear of Missing Out dalam Tren Wisata Berbasis Media Sosial: Studi tentang Peningkatan Kunjungan di Agroeduwisata MarkazKomobidd - Almayla Adzra Faiza; Aliudin Aliudin; Dwi Novita Lestari; Desita Putri Rahmawati; Avrilya Indah Riyantika; Anindya Widyariesta (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study investigates the influence of Fear of Missing Out (FoMO), a psychological phenomenon amplified by social media platforms such as Instagram and TikTok, on the behavior of each individual. Focusing on the case of Agroeduwisata MarkazKomobid in Serang Regency, this study uses qualitative methods to explore how digital exposure shapes travel motivation. Referring to insights on digital culture, the psychological effects of FoMO, and social media-driven tourism strategies, this analysis reveals that online trends often serve as social benchmarks, pressuring individuals to engage in experiences that are considered popular or viral. These findings emphasize the strategic importance of social media in creating an attractive destination image and driving visitor interest, especially for active social media users.